Neurodisability and the criminal justice system comparative and therapeutic responses (Cheltenham Edward Elgar Publishing, 2021)
This thought-provoking book highlights the increasing recognition of the prevalence of neurodisability within criminal justice systems, discussing conditions including intellectual, cognitive and behavioural impairments, fetal alcohol spectrum disorders and traumatic and acquired brain injury. International scholars and practitioners demonstrate the extent and complexity of the neurodisability experience and present practical solutions for criminal justice reform. Examining the growing body of evidence which illustrates the significant over-representation of neurodisability amongst prison and juvenile justice populations, this critical book explores the challenges faced by people with a neurodisability who come into contact with the justice system. These challenges include: difficulty understanding interactions with police, navigating court processes, comprehending sentencing orders, and coping with prison and post-release life, which can lead to repeat victimisation and criminalisation. Overall, this book establishes that justice systems are often unable to meet the specific needs of people with a neurodisability and that there is a significant lack of appropriate support within the community aimed at prevention and diversion. Providing broad interdisciplinary insights, this timely book will prove a vital resource for scholars and students of criminal law, law and society, criminology, neuroscience and social work. It will also be of value to legal practitioners, law enforcement, prison employees and welfare professionals engaged with individuals with a neurodisability."--Page 4 of cover.
Part I: Understanding and responding to neurodisability. Neurodisability and the criminal justice system: a problem in search of a solution Gaye T. Lansdell, Bernadette Saunders, Anna Eriksson -- Neurodisability: a criminal law doctrine that is not pure insanity Amanda C. Pustilnik -- A public law model for cognitive-communication risk Joseph Wszalek -- Access to justice and the Convention on the Rights of Persons with Disabilities (CRPD) - an Australian perspective Penelope Weller -- Part II: Needs of young people with neurodisability. Dismantling barriers to justice for children affected by neurodisability Frances Sheahan, Nathan Hughes, Huw Williams, Prathiba Chitsabesan -- Neurodisability and trauma in children and young people in contact with the law Huw Williams, Leigh Schrieff, Nathan Hughes, James Tonks, Prathiba Chitsabesan, Hope Kent -- Protecting vulnerable child defendants in England and Wales: a house of cards? Shauneen Lambe and Kathryn Hollingsworth -- Fetal alcohol spectrum disorder and the criminal justice system Hayley Passmore and Sharynne Hamilton -- Part III: Responses to neurodisability within the criminal justice system. What do lawyers really know about neurodisability? Confusion, obfuscation and dereliction of duty Gaye T. Lansdell, Bernadette Saunders, Anna Eriksson, Rebecca Bunn -- Towards dignity: better court pathways for people with lived experience of acquired brain injury Magistrate Pauline Spencer -- Neurodisability and the 'revolving' prison door: an international problem viewed through an Australian lens Anna Eriksson, Bernadette Saunders, Gaye T. Lansdell -- An interdisciplinary call for action Bernadette Saunders, Anna Eriksson, Gaye T. Lansdell.
Includes bibliographical references and index.
Keywords: Criminal justice, Administration of. -- Electronic book; Criminal liability; Developmentally disabled; Criminal justice, Administration of; Criminal liability; Developmentally disabled